A multifunctional covalently linked graphene–MOF hybrid as an effective chemiresistive gas sensor. Issue 32 (6th August 2021) - Jayaramulu, Kolleboyina; Esclance DMello, Marilyn; Kesavan, Kamali; Schneemann, Andreas; Otyepka, Michal; Kment, Stepan; Narayana, Chandrabhas; Kalidindi, Suresh Babu; Varma, Rajender S.; Zboril, Radek; Fischer, Roland A.
Abstract : The covalent linkage of graphene acid (GA) with amine-functionalized UiO-66-NH2 via an amide bond. The resultant hybrid GA@UiO-66-NH2 acts as a chemiresistive CO2 sensor wth significant efficiency owing to its unique structural features. Abstract : A hybrid of GA@UiO-66-NH2 was synthesized based on the covalent assembly of graphene acid (GA) and the amine functionalized UiO-66 metal–organic framework through amide bonds. This strategy endows the material with unique properties, such as hierarchical pores, a porous conductive network decorated with functional groups, a high specific surface area, and a good chemical and thermal stability. The resultant hybrid has an electrical resistance of ∼10 4 Ω, whereas the pristine GA and UiO-66-NH2 possess an electrical resistance of ∼10 2 Ω and ∼10 9 Ω, respectively. The hybrid GA@UiO-66-NH2 was demonstrated for CO2 chemiresistive sensing and displayed a very fast response and quick recovery time of ∼18 s for 100% CO2, at 200 °C. While the pristine GA exhibits negligible response under the same conditions, GA@UiO-66-NH2 exhibited a response of 10 ± 0.6%. Further, in situ temperature dependent Raman studies during CO2 exposure confirm the presence of strong hydrogen bonding interaction between CO2 and the amide functionality present on GA@UiO-66-NH2 . The resulting gas sensing characteristics of GA@UiO-66-NH2 are majorly attributed to the better interaction of CO2 at the amide/amine functional groups and the readily accessible hierarchical pores. This design strategy opens new horizons in the development of covalently linked hybrids with hierarchical porous conductive networks which can help to improve the gas sensing properties of MOF-based materials.